Advanced three-dimensional scan methods in the nanopositioning and nanomeasuring machine - Hausotte, Tino; Percle, Brandon; Jäger, Gerd (Measurement Science & Technology, 2009)
The nanopositioning and nanomeasuring machine developed at the Ilmenau University of Technology was originally designed for surface measurements within a measuring volume of 25 mm x 25 mm x 5 mm. The interferometric length measuring and drive systems make it possible to move the stage with a resolution of 0.1 nm and a positioning uncertainty of less than 10 nm in all three axes. Various measuring tasks are possible depending on the installed probe system. Most of the sensors utilized are one-dimensional surface probes; however, some tasks require measuring sidewalls and other three-dimensional features. A new control system, based on the I++ DME specification, was implemented in the device. The I++ DME scan functions were improved and special scan functions added to allow advanced three-dimensional scan methods, further fulfilling the demands of scanning force microscopy and micro-coordinate measurements. This work gives an overview of these new functions and the application of them for several different measurements.
Keywords: nanomeasuring machine; scanning probe microscopy; micro CMM; nano CMM; coordinate measurement; free-form scan